Is Byzantine studies a colonialist discipline? toward a critical historiography - Anderson, Benjamin; Ivanova, Mirela 1962- (The Pennsylvania State University Press, 2023)
"A volume of essays by scholars of Byzantine art, history, and literature addressing the entanglements between the academic discipline of Byzantine studies and the practice and legacies of European colonialism"--
Auf dem Cover als Herausgeber bezeichnet
Keywords: Geschichtsschreibung; Methode; Kolonialismus; Kunstgeschichtsschreibung; Byzantinistik; Imperialism / Historiography; Byzantine Empire / Study and teaching / Historiography; Europe / Colonies / Historiography; Historiography; Byzantine Empire; Essays; Aufsatzsammlung